A Training Model of Epidemic Development - Liapzev, Alexander V. (Computer Tools in Education, 2020)
A training model describing the development of the epidemic in a limited community of individuals is proposed. The main “rigid” model contains only one parameter, which allows it to be used in the educational process as an exercise in mathematical modeling. Qualitative conclusions resulting from numerical calculations based on this model are discussed. We also discuss the “softening” of the model, which allows us to qualitatively analyze some aspects in relation to the epidemic developing in human society.